Implementasi Model Pembelajaran â€œTreffingerâ€ untuk Meningkatkan Kreativitas dan Kemampuan Pemecahan Masalah Siswa SMA - Nugraheni, Savira; Sugianto, Sugianto; Rusilowati, Ani (UPEJ Unnes Physics Education Journal, 2019)
This study aims to determine the increase in creativity and students problem solving abilities after applying the ?Treffinger? learning model. This type of research is quantitative research. The design of this study was a quasi-experiment with non-equivalent control group design. The research instruments in the form of creativity test and problem solving abilities test is an essay question. The study population was all students of class X MIPA SMA Negeri 2 Kudus in 2017/2018 Academic Year. The sampling technique was purposive sampling.  The experimental class treated with ?Treffinger? learning model and control class with conventional learning (lecture). The analysis technique uses gain test, t test, Kolmogorov-Smirnov test, and simple linear regression. The results showed an increase in creativity and problem-solving ability of the experimental class was greater than the control class. Student creativity has a positive effect on their problem solving ability by 46.1%.